The Effect of Price, Needs and Scarcity on Purchasing Decisions for 3 Kg Lpg Gas Among the People of Bengkalis - Suci Anggraini; Nageeta Tara Rosa (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study aims to analyze and see the effect of price, needs and scarcity on purchasing decisions for 3 kg LPG gas among the Bengkalis community. The research method of analysis used, namely multiple linear regression analysis with SPSS 27 tools. The sampling method in this study was non-probability sampling with purposive sampling technique. The number of samples in this study were 100 respondents. The results of this study indicate that the three variables of price, necessity and scarcity have a positive effect on purchasing decisions for 3 kg LPG gas in Bengkali both partially and together. Suggestions from this study are that the Government needs to pay attention to prices, needs and scarcity to increase people's buying intention for 3 kg LPG Gas in Bengkalis. It is better if the price of 3 kg LPG Gas needs to be adjusted to the community's income so that there is no scarcity of 3 kg LPG Gas and the community's need for 3 kg LPG Gas can be fulfilled properly and people's purchase intention will increase.